Bipolar Modulation in a Self‐Powered Ultra‐Wide Photodetector Based on Bi2Se3/AlInAsSb Heterojunction for Wavelength‐Sensitive Imaging and Encrypted Optical Communication - Han, Yajie; Jiao, Shujie; Zhang, Xiangyu; Rong, Ping; Zhao, Yue; Jiang, Dongwei; He, Wen; Wang, Dongbo; Gao, Shiyong; Wang, Jinzhong (Advanced materials (Weinheim), 2025)
Broadband photodetectors (PDs) have garnered significant attention due to their ability to detect optical signals across a wide wavelength range, with applications spanning military reconnaissance, environmental monitoring, and medical imaging. However, existing broadband detectors face several practical challenges, including limited detection range, uneven photoresponse, and difficult to distinguish multispectral signals. To address these limitations, this study presents a self‐powered ultra‐wide PD based on the Bi2Se3/AlInAsSb heterojunction. The device can detect signals across a wide wavelength range from 250 nm to 1900 nm, exhibiting outstanding optoelectronic performance with a maximum responsivity of 0.5 A W−1, a detectivity of 4.2 × 1012 Jones, a switching ratio of 1.1 × 104, and an external quantum efficiency of 71.4%. Furthermore, the detector achieves a detectivity greater than 1010 Jones across the entire broadband range, significantly improving photoresponse uniformity. Notably, due to the differential band alignment of the two materials across spectral ranges, this detector exhibits a photocurrent polarity reversal in the 650–680 nm range. Leveraging its broadband and bipolar characteristics, this PD successfully enables secure information encryption in communication systems. This study significantly advances broadband PD technology, enhancing its practical uses and introducing innovative solutions for secure communications, thus strengthening communication security and confidentiality. This work constructs a wavelength‐dependent, bipolarity‐modulated self‐powered ultra‐wide Bi2Se3/AlInAsSb heterojunction photodetector (PD) with a response range of 250–1900 nm, achieving a detectivity greater than 1010 Jones across the entire spectrum under zero bias. It also enables high‐contrast broad‐spectrum imaging and high‐encryption optical communication.